UUAT1 Is a Golgi-Localized UDP-Uronic Acid Transporter That Modulates the Polysaccharide Composition of Arabidopsis Seed Mucilage. Issue 1 (6th January 2017) - Saez-Aguayo, Susana; Rautengarten, Carsten; Temple, Henry; Sanhueza, Dayan; Ejsmentewicz, Troy; Sandoval-Ibañez, Omar; Doñas, Daniela; Parra-Rojas, Juan Pablo; Ebert, Berit; Lehner, Arnaud; Mollet, Jean-Claude; Dupree, Paul; et al.
Abstract : Screening of Arabidopsis mutants with altered seed mucilage allowed identification of UUAT1, a Golgi-localized protein that transports UDP-glucuronic acid and plays a role in the biosynthesis of pectin. Abstract: UDP-glucuronic acid (UDP-GlcA ) is the precursor of many plant cell wall polysaccharides and is required for production of seed mucilage. Following synthesis in the cytosol, it is transported into the lumen of the Golgi apparatus, where it is converted to UDP-galacturonic acid (UDP-GalA), UDP-arabinose, and UDP-xylose. To identify the Golgi-localized UDP-GlcA transporter, we screened Arabidopsis thaliana mutants in genes coding for putative nucleotide sugar transporters for altered seed mucilage, a structure rich in the GalA-containing polysaccharide rhamnogalacturonan I. As a result, we identified UUAT1, which encodes a Golgi-localized protein that transports UDP-GlcA and UDP-GalA in vitro. The seed coat of uuat1 mutants had less GalA, rhamnose, and xylose in the soluble mucilage, and the distal cell walls had decreased arabinan content. Cell walls of other organs and cells had lower arabinose levels in roots and pollen tubes, but no differences were observed in GalA or xylose contents. Furthermore, the GlcA content of glucuronoxylan in the stem was not affected in the mutant. Interestingly, the degree of homogalacturonan methylation increased in uuat1 . These results suggest that this UDP-GlcA transporter plays a key role defining the seed mucilage sugar composition and that its absence produces pleiotropic effects in this component of the plant extracellular matrix.